Cardiovascular side effects and toxicity of lithium usage in adults: A systematic review of case reports and observational studies - Rahmi, Koyuki Atifa; Khotimah, Husnul; Rohman, Mohammad Saifur (Heart Science Journal, 2025)
BACKGROUND: Lithium is a first-line treatment for Bipolar Affective Disorder, but it has a narrow therapeutic range and has been shown to have cardiovascular side effects. This study aimed to compile the cases of lithium-induced cardiovascular abnormalities and the pathological mechanisms behind those effects. OBJECTIVES: To conduct a systematic review of case reports in adult patients who experienced cardiovascular side effects of lithium in the last 11 years. METHODS: The PRISMA method was followed to search PubMed, Wiley Online Library, ResearchGate, Springer, Semantic Scholar, and Google Scholar databases for articles from January 2013 to June 2024 using combinations of 'lithium,' 'cardiac,' 'cardiovascular,' 'side effect,' 'patient,' and 'case.' Case reports and observational studies concerning lithium use were identified for cardiovascular side effects. RESULTS: Reported cardiovascular side effects of lithium included ECG abnormalities (N=31), myocarditis (N=1), cardiomyopathies (N=4), cardiac tamponade (N=1), thrombosis (N=1), and pulmonary hypertension (N=1). Lithium causes cardiovascular abnormalities via sodium channel blockage, interference with cardiac pacemaker cells, increased serum catecholamines and serotonin, disruption of thyroid gland functions, and induction of nephrogenic diabetes insipidus, leading to hemodynamic imbalance. CONCLUSION: Lithium precipitates cardiac side effects and toxicity through direct interference with the cardiac conduction system, disruption of metabolic hormones, and multi-organ interactions.